2013
DOI: 10.1007/s00464-013-2938-z
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoendoscopic single-site (LESS) varicocelectomy with reusable components: comparison with the conventional laparoscopic technique

Abstract: The LESSV procedure performed with the reusable X-Cone is as safe and efficient as MLV. After LESSV, the parameters measuring postoperative patient satisfaction are significantly improved. Given its reusable components, including prebent laparoscopic instruments, the X-Cone platform is a cost-effective alternative to disposable or homemade single ports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 19 publications
3
31
0
2
Order By: Relevance
“…So, regarding the success of varicocelectomy, our data suggests that SIL-V is as safe and effective as CTL-V. Similar findings were reported in a retrospective study by Friedersodroff et al [13] which included 20 patients with left-sided varicocele subjected to SIL-V compared to 79 patients subjected to CTL-V.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…So, regarding the success of varicocelectomy, our data suggests that SIL-V is as safe and effective as CTL-V. Similar findings were reported in a retrospective study by Friedersodroff et al [13] which included 20 patients with left-sided varicocele subjected to SIL-V compared to 79 patients subjected to CTL-V.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are supported by the recently published data that there is a lower inflammatory stimulus (IL-6) following SILS than that following conventional laparoscopic surgery especially in the early postoperative hours [18]. Previous two studies [12,13] comparing SIL-V and CTL-V reported that the two groups were comparable regarding postoperative pain at day 1. Park et al [23] concluded that SIL-V was found to cause less pain than open inguinal varicocelectomy in cases of bilateral disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the purpose of decreasing invasiveness and improving appearance, U-LESS was established, which represents an extension of the minimally invasive surgery. There were several reports showing that U-LESS varicocelectomy yielded superior cosmetic results with less pain compared with conventional laparoscopic varicocelectomy 8914…”
Section: Discussionmentioning
confidence: 99%
“…The patients who undergo the varicocelectomy are usually younger. They often place more importance on the number of incision scares than older patients 14. TTLVL need only two 5-mm ports which are less than that of CLVL with three ports.…”
Section: Discussionmentioning
confidence: 99%